The Importance of the Risk in Public Passenger Transport Financing - Poliak, Milos; Semanova, Stefania; Varjan, Peter (Communications - Scientific letters of the University of Zilina, 2014)
The paper deals with the importance of the risk in financing public passenger transport. The first part analyses the risks affecting financing public passenger transport. These risks can be divided into two basic groups: cost risks and revenue risks. The second part describes the ways of dividing risks between contractual parties. The risk determination in financing public passenger transport is discussed in the last part of the paper